2021
DOI: 10.1186/s12909-021-03029-4
|View full text |Cite
|
Sign up to set email alerts
|

Residency training amid the COVID-19 pandemic: exploring the impact on mental health and training, a lesson from Iran

Abstract: Background COVID-19 has affected the training programs and the clinical schedules of surgical wards in many countries, including Iran. Also, the continuous involvement with COVID-19 patients has caused stress in health care workers; among them, residents are on the frontlines of care delivery. Therefore, we designed a study to assess the mental effects of these circumstances, and the effects on General Surgery and Obstetrics & Gynecology residency training in the busiest surgical department… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…If it is not suitable, there would be emotional problems such as trance, inability to concentrate, and disgust. (iii) e psychological reaction in physical education is a special behavior, therefore, the psychological training in physical education cannot be carried out blindly; otherwise, it would lead to emotional problems for students [16]. In competitive activities, taking badminton as an example, the characteristics of athletes' psychological reactions are mainly singles and doubles.…”
Section: Types Of Obstacles In Mental Trainingmentioning
confidence: 99%
“…If it is not suitable, there would be emotional problems such as trance, inability to concentrate, and disgust. (iii) e psychological reaction in physical education is a special behavior, therefore, the psychological training in physical education cannot be carried out blindly; otherwise, it would lead to emotional problems for students [16]. In competitive activities, taking badminton as an example, the characteristics of athletes' psychological reactions are mainly singles and doubles.…”
Section: Types Of Obstacles In Mental Trainingmentioning
confidence: 99%
“…A cross-sectional study conducted in China revealed that medical personnel experienced anxiety and melancholy during the pandemic, and reported the potential benefits of psychological support and group therapy ( 21 ). In Iran, a cross-sectional study using an online questionnaire investigated the deleterious effects of COVID-19 on the education and mental health of general surgery and obstetrics/gynecology trainees ( 22 ). Similarly, in Italy, a survey ( 23 ) highlighted the negative impact of the pandemic on obstetrics and gynecology training programs and proposed innovative solutions to mitigate the deficiencies in training caused by COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of the specialty or function at that moment, physicians who worked in urgencies and emergencies stood out in the attempt to save lives, a surprising situation in the health system. Similar situations took place all over the world, such as in Iran, which redirected all the medical specialties and sub-specialties offered in the reference hospitals to COVID-19 management (Moini et al, 2021). Mathematical models to reorganize the workforce were also studied, as well as strategies such as alternating medical teams to enhance productivity and protection (Sánchez-taltavull et al, 2021).…”
Section: Discussionmentioning
confidence: 99%